Plant-Based Diets Are Associated With Lower Adiposity Levels Among Hispanic/Latino Adults in the Adventist Multi-Ethnic Nutrition (AMEN) Study - Singh, Pramil N.; Jaceldo-Siegl, Karen; Shih, Wendy; Collado, Nancy; Le, Lap T.; Silguero, Krystal; Estevez, Dennys; Jordan, Michael; Flores, Hector; Hayes-Bautista, David E.; McCarthy, William J. (Frontiers in Nutrition, 2019)
Background: The Hispanic/Latino population in the US is experiencing high rates of obesity and cardio-metabolic disease that may be attributable to a nutrition transition away from traditional diets emphasizing whole plant foods. In the US, plant-based diets have been shown to be effective in preventing and controlling obesity and cardio-metabolic disease in large samples of primarily non-Hispanic subjects. Studying this association in US Hispanic/Latinos could inform culturally tailored interventions. Objective: To examine whether the plant-based diet pattern that is frequently followed by Hispanic/Latino Seventh-day Adventists is associated with lower levels of adiposity and adiposity-related biomarkers. Methods: The Adventist Multi-ethnic Nutrition Study (AMEN) enrolled 74 Seventh-day Adventists from five Hispanic/Latino churches within a 20 mile radius of Loma Linda, CA into a cross-sectional study of diet (24 hour recalls, surveys) and health (anthropometrics and biomarkers). Results: Vegetarian diet patterns (Vegan, Lacto-ovo vegetarian, Pesco-vegetarian) were associated with significantly lower BMI (24.5 kg/m2 vs 27.9 kg/m2, p=0.006), waist circumference (34.8 cm vs 37.5cm , p=0.01), and fat mass (18.3 kg vs 23.9 kg, p=0.007), as compared to non-vegetarians. Adiposity was positively associated with pro-inflammatory cytokines (Interleukin-6) in this sample, but adjusting for this effect did not alter the associations with vegetarian diet. Conclusions: Plant-based eating as practiced by US-based Hispanic/Latino Seventh-day Adventists is associated with BMI in the recommended range. Further work is needed to characterize this type of diet for use in obesity-related interventions among Hispanic/Latinos in the US.